Rare and challenging case: a young woman with a pulmonary malignant peripheral nerve sheath tumor mimicking mesothelioma - Irawan, Ari; Agus Setyawan, Ungky; Dwi Pratiwi, Suryanti; Setyo Yudhanto, Hendy; Kusuma Wardhana, Koernia; Rachma Erawati, Dini (Malang Respiratory Journal, 2026)
Introduction: Malignant peripheral nerve sheath tumor (MPNST) is a rare and highly aggressive tumor that develops from peripheral nerves which is closely related to neurofibromatosis type 1 (NF1). It has a very small percentage of occurrence in the lung. Here, we would like to report a case of pulmonary MPNST mimicking mesothelioma that was treated with cisplatin-pemetrexed. Case Illustrations: A 17-year-old female with no history of NF1, complaints of shortness of breath, and weight loss. A thoracic CT-scan and pathology were initially consistent with suspected mesothelioma. A unique finding in this case, was demonstrated positive vimentin and CD56, also loss of nuclear SOX10 and H3K27me3 expression in spindle cells. After a multidisciplinary board discussion, the diagnosis of MPNST was assumed. She underwent a palliative chemotherapy regimen. Discussion: Pulmonary MPNST with or without NF1 seems infrequent. Its clinical findings are usually nonspecific with a complex histological appearance. Establishing the diagnosis of MPNST is challenging, therefore pathological examination and immunohistochemistry (IHC) become the gold standard. The expression of SOX10 has poor sensitivity, also the loss of S100 expression may indicate de-differentiation of Schwann cells, hence, it may be less specific for MPNST diagnosis. Nevertheless, the loss of H3K27me3 marker has a great diagnostic value. The most effective treatment is complete surgical resection to achieve negative margins. However, in our case, the tumor has metastasized and is unresectable, so she was treated with the cisplatin-pemetrexed chemotherapy regimen and obtained stable disease results on the RECIST-CT examination after 3-series-chemotherapy. Conclusion: MPNST is a rare case with difficulties in diagnosis due to nonspecific clinical and histological features, therefore, IHC plays an important role in providing its diagnosis. Chemotherapy might be a good approach for treating an unresectable MPNST, but, still, there is no gold standard for palliative care guidelines.